Characteristics of select and non-select U15 male soccer players - Konarski, J.; Krzykala, M.; Skrzypczak, M.; Nowakowska, M.; Coelho-e-Silva, M.; Cumming, S.; Malina, R. M. (Biology of Sport, 2021)
Baseline characteristics of 31 healthy male U15 soccer players who were classified as select or non-select at the end of the season were compared. Players were 14.4 ± 0.54 years (13.6-15.3 years) at baseline; characteristics included body size, proportions and composition, estimated maturity status, several functional capacities, and coach classifications of potential in the sport. Decisions regarding selection or nonselection were made about two months after baseline. Select and non-select U15 soccer players differed significantly in estimated maturity status, body size, proportions and estimated muscle mass, functional tests related to speed, power and strength, and coach evaluation of potential, specifically tactical skills on offense and skills associated with creativity and decision making. When age and biological maturity status were statistically controlled, select and non-select players differed significantly only on the vertical jump, grip strength, and coach ratings of tactical skills on offense and of creativity and decision making. Results of stepwise discriminant analysis highlighted the importance of coach evaluation of tactical skills associated with offense, and of power and strength in distinguishing select from non-select players. The results highlight the dvantages of advanced biological maturity status among adolescent male soccer players and also the importance of oach perceptions of talent. The latter implies a need for further study of the basis of coach perceptions, specifically how they are influenced by and perhaps interact with player characteristics at different ages, and how the perceptions influence playing time and player behaviors and interactions.